Glutathione S-conjugates as prodrugs to target drug-resistant tumors - Ramsay, Emma E.; Dilda, Pierre J. (Frontiers in Pharmacology, 2014)
Living organisms are continuously exposed to xenobiotics. The major phase of enzymatic detoxification in many species is the conjugation of activated xenobiotics to reduced glutathione (GSH) catalyzed by the glutathione-S-transferase (GST). It has been reported that some compounds, once transformed into glutathione S-conjugates, enter the mercapturic acid pathway whose end products are highly reactive and toxic for the cell responsible for their production. The cytotoxicity of these GSH conjugates depends essentially on GST and γ-glutamyl transferases (γGT), the enzymes which initiate the mercapturic acid synthesis pathway. Numerous studies support the view that the expression of GST and γGT in cancer cells represents an important factor in the appearance of a more aggressive and resistant phenotype. High levels of tumor GST and γGT expression were employed to selectively target tumor with GST- or γGT-activated drugs. This strategy, explored over the last two decades, has recently been successful using GST-activated nitrogen mustard (TLK286) and γGT-activated arsenic-based (GSAO and Darinaparsin) prodrugs confirming the potential of GSH-conjugates as anticancer drugs.